ANALISIS PENGARUH SUHU DAN KONSENTRASI LARUTAN CaCl2 TERHADAP KUALITAS FISIK TERUNG UNGU (Solanum melongena L.) SELAMA PENYIMPANAN - Lestari, Hanis Adila; Prabowo, Amas Agung Pandu; Soolany, Christian; Kurniawan, Anri (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2025)
Purple eggplant (Solanum melongena L.) is a type of plant known as a vegetable that is used as a food ingredient. After purple eggplants are harvested, they still carry out metabolic processes such as respiration and transpiration. Inhibition of respiration in agricultural products can be done by cold air storage combined with dipped in CaCl2 as a pretreatment. The purpose of this study is to determine how the physical characteristics of purple eggplant are affected by temperature and CaCl2 solution concentration. The method used was a Completely Randomized Design (CRD) with two factors. The first factor is storage temperature, which consists of 9 °C and room temperature. The second factor is the CaCl2 concentration, consisting of 0%, 1%, and 2%. The parameters observed during storage were weight loss, texture, and total dissolved solids. This research was carried out for 4 days of storage and measured every day with 3 replication. The results show that dipping purple eggplant in CaCl2 and cold storage can inhibit the respiration and transpiration processes. The best treatment is to dip it in 2% CaCl2 and store it in the refrigerator.